Avalanche! - Shackleton, Caroline; Turner, Nathan Paul (New YORK Cambridge University Press, 2014)
Avalanches are frightening natural disasters that can seem to come out of nowhere. There are things that you can do to increase your chances of survival, though. This reader explores one of the worst avalanches in history and discusses the causes of such disasters.
Keywords: English language Textbooks for foreign speakers; Readers (Primary); Readers (Elementary); Avalanches Juvenile literature; Textbooks for foreign speakers